An Overview of Beriberi - Pereira, Amanda Gomes [UNESP]; Cunha, Letycia Netto de Paula [UNESP]; Paiva, Sergio Alberto Rupp [UNESP]; Azevedo, Paula Schmidt [UNESP]; Zornoff, Leonardo Antônio Mamede [UNESP]; Polegato, Bertha Furlan [UNESP]; Costa, Nara Aline; Minicucci, Marcos Ferreira [UNESP] (Karger Publishers, 2025)
Beriberi is a nutritional disorder caused by thiamine deficiency. Classically, Beriberi presents in two primary clinical forms: "wet" Beriberi, which features heart and circulatory system impairment, and "dry" Beriberi, which causes polyneuropathy. Although it is an easily treatable condition, it is often misdiagnosed and can be life-threatening if not promptly recognized and managed. The diagnosis of Beriberi is performed by the signs and symptoms of the disease and can be confirmed by thiamine deficiency identification or by therapeutic testing. However, considering the costs and the limitations of the assays to evaluate thiamine deficiency, the diagnosis based on the evaluation of clinical signs and symptoms and the therapeutic test could eliminate the need for measuring serum thiamine levels. Regarding treatment, immediate thiamine administration in the presence of clinical manifestations of the disease is recommended. Overall, 100-300 mg daily doses are enough to improve symptoms. In this review, we aim to (1) provide a clinical update about how to identify and treat the Beriberi and (2) describe the historical perspective, pathophysiological mechanisms, and other relevant aspects which may have applications in clinical management of Beriberi.